La labellisation, (re)qualification ou disqualification des marges ? Le cas du safran à Taliouine (Anti-Atlas, Maroc) - Mari Oiry Varacca (Revue de Géographie Alpine)
This article examines how agricultural products from marginalised mountain regions in Morocco manage to get labels. The country’s public authorities present labelling as a new way of requalifying areas that have previously been left behind. They do this by recognising the areas’ uniqueness and the quality of their certified products. However, this labelling can also exacerbate differences between spaces, revalue some, disqualify others, exclude certain actors and stir up conflicts. A critical reading of these labelling processes is offered here. Are these processes really capable of shrinking not only a particular space’s marginality but also social inequality? The discussion focuses on the labelling of saffron from Taliouine, a region in southern Morocco that has long been neglected by the public authorities to such a degree that it is a land of emigration. The article considers how different representations of the territory and agricultural knowledge are negotiated through the labelling process. It analyses the perspectives of ordinary players: small farmers who view themselves as being excluded from the process. Beyond the tensions that are revealed and amplified by the labelling, this work shows the arrangements and ways of resisting that are found in order to “make do with” labelling and fight against marginalisation – sometimes without having a label.